The Role of Ethical Practices in Supply Chain Management: A Case Study of The KwaZulu-Natal Department of Health - Lethokuhle Dladla; Strinivasan Pillay; Eustache Tanzala Kikasu (Politeia, 2026)
Unethical practices in the public sector procurement continue to undermine transparency, fairness, and service delivery. Persistent challenges such as political interference, lack of oversight, and limited ethics training in the public sector have raised concerns over the integrity of Supply Chain Management (SCM) processes. This study is driven by the imperative to strengthen ethical standards within SCM and to address persistent systemic deficiencies that undermine adherence to procurement regulations. A qualitative research design was employed, utilising semi-structured interviews to gather data from SCM officials across junior, middle, and supervisory levels. Thematic analysis was conducted with the aid of NVivo 15 software to systematically identify recurring patterns and extract meaningful insights. The study found that fairness, transparency, and accountability are critical in improving procurement efficiency, fostering stakeholder trust, and reducing risks such as corruption, fraud, and bid manipulation. However, political and managerial interference, resource constraints, resistance to change, and inadequate ethics training were major contributors to unethical conduct. The implementation of ethical practices in SCM catalyses enhanced compliance and effectiveness in promoting service delivery. Lack of capacity among SCM practitioners and political influences are key areas that lead to unethical practices. The study recommends a multi-dimensional ethical governance framework, which provides a structured approach to embedding ethical principles within supply chain operations. The framework emphasises proactive risk management, transparency, corporate governance, and the use of technology-driven monitoring systems to uphold procurement integrity.